STRESS IN ALEX MICHAELIDAS’ NOVEL THE SILENT PATIENT - Mai Sarah; Asnani Asnani (JOURNAL OF LANGUAGE, 2021)
The study focuses on the stress experienced by the protagonist, Alicia Berenson. The main purpose of this study is to determine the types and the impacts of stress experienced by the protagonist by the name of Alicia Berenson, based on the theory of stress proposed by Priyoto (2014). In analyzing The Silent Patient, the researchers use qualitative research method to process and arranges the data. The data collected are divided into two categories i.e. primary data and secondary data. The primary data is the novel The Silent Patient (2019), and the researchers find fifteen data to be included in the analysis. The secondary data are books and other sources related to the analysis such as books or journals of stress issues, literary theory, the author’s biography, internet and other relevant information to the analysis of this research paper. The data are collected through library research and searched based on the explanation from types and the impact of Stress proposed by Priyoto. The results of the study show the following conclusion. First, Alicia suffers from chronic stress which can be shown through impaired social relationships and nervousness. Second, the behavioral impact is shown through changes in the behavior system to be silent, aggressive behavior and self-injured.